2014
DOI: 10.2196/jmir.3176
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of a Web-Based Positive Psychology Program for Youth Mental Health: Randomized Controlled Trial

Abstract: BackgroundYouth mental health is a significant public health concern due to the high prevalence of mental health problems in this population and the low rate of those affected seeking help. While it is increasingly recognized that prevention is better than cure, most youth prevention programs have utilized interventions based on clinical treatments (eg, cognitive behavioral therapy) with inconsistent results.ObjectiveThis study explores the feasibility of the online delivery of a youth positive psychology prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 38 publications
3
99
0
4
Order By: Relevance
“…Higher subjective wellbeing is also associated with superior peer, parental, and teacher relationships and higher levels of self-esteem and self-efficacy (Gilman and Huebner, 2006). In adolescents, PP interventions have been shown to decrease depression and stress symptoms and increase overall wellbeing (Manicavasagar et al, 2014;Norrish and Vella-Brodrick, 2009). While ACT promotes mindfulness as a means to manage negative thoughts and emotions, PP promotes mindfulness to increase positive emotions in order to improve subjective wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Higher subjective wellbeing is also associated with superior peer, parental, and teacher relationships and higher levels of self-esteem and self-efficacy (Gilman and Huebner, 2006). In adolescents, PP interventions have been shown to decrease depression and stress symptoms and increase overall wellbeing (Manicavasagar et al, 2014;Norrish and Vella-Brodrick, 2009). While ACT promotes mindfulness as a means to manage negative thoughts and emotions, PP promotes mindfulness to increase positive emotions in order to improve subjective wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…The exercises are simple enough such that written directions for various PPIs can be integrated into myriad forms of counseling including individual, group, and web-based programs. Prior research has shown that clinicians are not required for administration of PPIs [56, 67, 69, 70]; in fact, a recent study found that completing PPIs by text messaging, without any clinical contact, was associated with greater reductions in depressive symptoms compared to control text messaging among those with elevated depressive symptoms [71]. Because text messaging is so widely available and because the clinical training and oversight needed to deliver PPT-S+ is quite modest, we believe the potential public health impact of PPT-S+ could be substantial if the results of this clinical trial show efficacy for smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of an online positive psychology program (Bite Back) for the improvement of the well-being and mental health in a sample of Australian youth have been examined. Conclusions showed that this program decreased symptoms of depression and stress and increased well-being in young people, especially for those who used the website for 30 minutes [29].…”
Section: Effectiveness Of Web-based Psychotherapy In Individuals mentioning
confidence: 93%